K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

30 tháng 7 2021

\(8x^3-\frac{1}{27}\)

\(\left(2x\right)^3-\left(\frac{1}{3}\right)^3\)

\(\left(2x-\frac{1}{3}\right)\left(4x^2+\frac{2}{3}x+\frac{1}{9}\right)\)

19 tháng 9 2021

x2 - z2 + y2 - 2xy

= (x2 - 2xy + y2 )- z2

= (x-y)2 - z2

= (x-y-z)(x-y+z) 

31 tháng 8 2021

\(16-8x+x^2\)
\(=4^2-2.4.x+x^2\)
\(=\left(4-x\right)^2\)

22 tháng 7 2021

uuuttyutyyuyuyyuyuyuyuyuyuyuy

NM
23 tháng 7 2021

a.\(x^3-8=x^3-2^3=\left(x-2\right)\left(x^2+2x+4\right)\)

b.\(27x^3+125y^3=\left(3x\right)^3+\left(5y\right)^3=\left(3x+5y\right)\left(9x^2-15xy+25y^2\right)\)

c.\(\left(2x-1\right)^3+8=\left(2x-1\right)^3+2^3=\left(2x+1\right)\left[\left(2x-1\right)^2-2\left(2x-1\right)+4\right]\)

d.\(x^6+6^3=\left(x^2+6\right)\left(x^4-6x+36\right)\)

e.\(1-27x^3=1-\left(3x\right)^3=\left(1-3x\right)\left(1+3x+9x^2\right)\)

j.\(\left(x-3\right)^3-27=\left(x-3\right)^3-3^3=\left(x-6\right)\left[\left(x-3\right)^2+3\left(x-3\right)+9\right]\)

g.\(x^3y^3+125=\left(xy\right)^3+5^3=\left(xy+5\right)\left(x^2y^2-5xy+25\right)\)

t.\(8x^3-\frac{1}{8}=\left(2x\right)^3-\left(\frac{1}{2}\right)^3=\left(2x-\frac{1}{2}\right)\left(4x^2+x+\frac{1}{4}\right)\)

u.\(x^3+\frac{1}{27}=x^3+\left(\frac{1}{3}\right)^3=\left(x+\frac{1}{3}\right)\left(x^2-\frac{x}{3}+\frac{1}{9}\right)\)

NM
23 tháng 7 2021

a.\(27x^3+27x^2+9x+1=\left(3x+1\right)^3\)

b.\(x^3-6x^2+12x-8=\left(x-2\right)^3\)

c.\(8x^3+12x^2+6x+1=\left(2x+1\right)^3\)

19 tháng 9 2021

x4-x3-x2+1

=x3(x-1)-(x2-1)

=x3(x-1)-(x-1)(x+1)

=(x-1)(x3-x-1)

\(5x^3-5x^2y-10x^2+10xy=5x^2\left(x-y\right)-10x\left(x-y\right)=5x\left(x-2\right)\left(x-y\right)\)

19 tháng 9 2021

x3 - 3x2 - 4x + 12

= x2(x-3) - 4(x-3)

= (x-3)(x2 -4)

=(x-3)(x-2)(x+2)

\(x^3-3x^2-4x+12\)

\(=\left(x^3-3x^2\right)-\left(4x-12\right)\)

\(=x^2\left(x-3\right)-4\left(x-3\right)\)

\(=\left(x^2-4\right)\left(x-3\right)\)

\(=\left(x-2\right)\left(x+2\right)\left(x-3\right)\)

1 tháng 11 2023

5²y² + 10xy³ - 20xy²

= 5y.(5y + 2xy² - 4xy)